Effects of cannabinoids in Amyotrophic Lateral Sclerosis (ALS) murine models: a systematic review and meta‐analysis. Issue 2 (18th January 2019) - Urbi, Berzenn; Owusu, Maame Amma; Hughes, Ian; Katz, Matthew; Broadley, Simon; Sabet, Arman
Abstract: Amyotrophic Lateral Sclerosis (ALS) is a neurodegenerative disorder that results from motor neuron damage. Cannabinoids have been proposed as treatments for ALS because of their anti‐excitotoxicity, anti‐oxidant and anti‐inflammatory effects. Preclinical studies in mice models of ALS have been published using a range of cannabinoid formulations and doses. To date, there has been no rigorous evaluation of these trials to assess a potential cannabinoid treatment effect. This review and meta‐analysis was undertaken to provide evidence for or against a treatment effect of cannabinoids in murine ALS models. Evidence of a treatment effect in mice may provide motivation for trials in human ALS. We identified a total of 10 studies; nine studies using cannabinoid treatment in transgenic SOD1‐G93A ALS‐model mice and one study in TDP‐43 transgenic mice. Eight of the nine studies that used SOD1‐G93A mice expressed similarly high copy numbers of the transgene while one study used a low‐copy number line. Outcomes evaluated were survival time and disease progression. The latter was measured by motor function and bodyweight decline. Meta‐analysis of the mean difference in survival time across the seven studies showed an increase in survival of 3.84 days (95% CI: 0.35–7.32 days; p = 0.031) for cannabinoid treated compared to control SOD1‐G93A mice. It was not possible to conduct meta‐analyses for motor function decline or weight loss. However, eight of nine studies reported significant improvements in measures of motor function decline and one reported non‐significant improvements. Weight loss was significantly attenuated in four of five studies reporting this measure while the other study reported a non‐significant attenuation. This review provides some evidence for the efficacy of cannabinoids in prolonging survival time in an ALS mouse model. A delay in disease progression is also suggested following cannabinoid treatment though it was not possible to consolidate the results from reviewed studies. However, studies have moderate to high risk of bias and are highly heterogeneous. Although this review provides some evidence to support the conduct of a cannabinoid trial in human ALS, more standardized studies on specific cannabinoids are necessary before supporting therapeutic potential of cannabinoids in treating patients with ALS. Open science badges: This article has received a badge for *Preregistration* because the study was pre‐registered athttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=89274 . The complete Open Science Disclosure form for this article can be found at the end of the article. More information about the Open Practices badges can be found athttps://cos.io/our-services/open-science-badges/ . Read the Editorial Highlight for this article on page 168 . Abstract : Meta‐analysis of pre‐clinical studies suggests cannabinoid receptor agonists may improve survival time. Meta‐analysis of the mean difference in survival time across the 7 studies showed an increase in survival of 3.84 days (95% CI 0.35 to 7.32 days; p = 0.031) for cannabinoid treated compared to control SOD1‐G93A mice. This review provides some evidence for the efficacy of cannabinoids in prolonging survival time in an ALS mouse model. This manuscript was awarded with the Pre‐registration Badge. The pre‐registration protocol can be accessed athttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=89274 . For more information see:https://cos.io/our-services/open-science-badges/ Read the Editorial Highlight for this article on page 168 .